The concept of social responsibility in non-governmental organizations = Koncepcja społecznej odpowiedzialności w organizacjach pozarządowych - Łoś-Tomiak, Anna; Dalecka, Magdalena (Zielona Góra: Faculty of Economics and Management Press)
The paper presents the idea of social responsibility, which is adequate for modern and efficient management of the enterprise. The analysis of the interdependence of the market and non-governmental sector has been made. The article includes the presentation of the justification for the existence of non-profit institutions as the entities that bridge the gap between the sector of enterprises and the state. The attempt has been made to prove that the universal principles, typical of corporate social responsibility, could be also applied in the management of non-governmental sector entities.
Keywords: społeczna odpowiedzialność biznesu; społeczna odpowiedzialność organizacji; organizacja pozarządowa; organizacja non-profit; corporate social responsibility; social responsibility of organization; non-governmental organization; non profit organization